Diagnostic Challenge of Lupus with Overlap Syndrome in an Adolescent: A Case Report - Anu Suria Ganason; Mohd Radzniwan A Rashid; Fathima Begum Syed Mohideen; Sharifah Najwa Syed Mohamad; Nurul Hayati Chamhuri (Universiti Sains Islam Malaysia, 2024)
Malaysian Journal of Science Health & Technology, Volume 10 Issue 2) Page (147–151)